PENERAPAN PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA SUB POKOK BAHASAN PERBANDINGAN DAN SKALA DI SMP NEGERI 3 ARJASA KELAS VII B SEMESTER GANJIL TAHUN AJARAN 2012/2013 - Rahmi, Ika; Trapsilasiwi, Dinawati; Sri L., Nurcholif Diah (Kadikma, 2012)
Abstract. Realistic Mathematics Education (RME) is solutions using contextual problem to develop students’ creative ideas. The characteristics of RME are using context, using model, using students own production and construction, interactivity, and intertwining. The subjects of the research were grade VII B students of SMP Negeri 3 Arjasa. The result of data analysis method shows that RME can be effectively used to increase student’s learning result. It can be seen from the increase in the average yield of classical learning which was 76,92% in the first cycle and 100% in the second cycle. The average result of students’ activity increased from 80,20% in the first cycle and 90,62% in the second cycle. Key Words : Realistic Mathematics Education (RME), the students’ activity and the result of study.